Abstracts Accepted for Publication 2017
DOI: 10.1136/annrheumdis-2017-eular.4166
|View full text |Cite
|
Sign up to set email alerts
|

AB1128 Helicobacter pylori in systemic lupus erythematosus its association with endoscopic and histopathologic findings

Abstract: BackgroundHelicobacter pylori (Hp) is a Gram-negative bacteria and the cause of most of the chronic gastric infections and its prevalence is above 50% worldwide. This infection is a well-known risk factor to gastric MALT lymphoma but also could be the trigger of several autoimmune diseases such as immune thrombocytopenic purpura and systemic lupus erythematosusObjectivesTo determine the frequency of H pylori in systemic lupus erythematosus patients (SLE).MethodsA cross-sectional study was done in patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Additionally, our study found that patients aged >65 years with HP infection had a lower risk of SLE but did not reach statistical significance. By contrast, one recent study by Prado et al showed high HP frequency in patients with SLE through endoscopic and histopathological findings (26). These investigations have some drawbacks, but most of them have shown a negative correlation between HP infection and SLE.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, our study found that patients aged >65 years with HP infection had a lower risk of SLE but did not reach statistical significance. By contrast, one recent study by Prado et al showed high HP frequency in patients with SLE through endoscopic and histopathological findings (26). These investigations have some drawbacks, but most of them have shown a negative correlation between HP infection and SLE.…”
Section: Discussionmentioning
confidence: 93%